A Peer Group Education Approach on Increasing Knowledge and Attitude of Adolescents Regarding Sexual Violence - Sasda, Musyahidah Mustakim; Amri, Ibnul Al Jauzi (Jurnal Ilmiah Kesehatan (JIKA), 2025)
Sexual violence is defined as any act targeting an individual's sexuality or sexual organs without consent, often involving coercion or threats. It constitutes a global public health concern with significant mental health consequences, particularly among adolescents as a vulnerable population, including those in Makassar, Indonesia. This study aimed to examine the effect of a peer group education approach on adolescents’ knowledge and attitudes regarding sexual violence. A quasi-experimental design with a non-equivalent control group and a pretest–posttest method was employed, involving 50 participants in the intervention group and 50 in the control group. Data were analyzed using the Mann–Whitney U test. The results showed a statistically significant difference between the intervention and control groups following the intervention, with p-values of 0,007 for knowledge (p-value <0,05) and 0,004 for attitude (p-value<0,05). These findings suggest that peer group education is an effective strategy for improving knowledge and fostering positive attitudes toward sexual violence among adolescents.